Legal Review of Victims Who Are Suspects in Theft Crimes: Analysis of Human Rights Protection in the Criminal Justice Process - Muhammad Reza; Ferawati Royani; Sandi Aprianto (CV. Utami, 2026)
This research aims to analyze the legal arrangements and forms of punishment for minors who are involved in narcotics abuse, as well as to identify the factors that cause children to fall into this action. This research is motivated by the increasing number of cases of narcotics abuse by children, which raises concerns regarding legal protection for children and the effectiveness of the juvenile criminal justice system in Indonesia. The research method used is a normative juridical method with a statutory approach, case studies. Data sources were obtained through literature studies of statutory regulations, literature books, scientific journals. The results of the research show that legal regulations regarding children involved in narcotics abuse have been contained in Law Number 35 of 2009 concerning Narcotics and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. However, in practice, the approach to punishment towards children still tends to be repressive. Diversion and rehabilitation have not yet become a complete priority. Apart from that, factors such as a non-conducive family environment, peer influence, social pressure, and weak legal education are factors that encourage children to abuse narcotics. This research recommends the need to strengthen the juvenile criminal justice system based on restorative justice, legal education for children and families, as well as cross-sector collaboration in preventing and handling juvenile and narcotics cases.